Transmission line fault detection and location using Wide Area Measurements - Das S.; Singh S.P.; Panigrahi B.K. (My University, 2025)
Knowledge of both voltage and current data is conventionally entailed for locating fault on transmission network. However, owing to the non-linearity of the system, the process becomes iterative and cumbersome. In order to address this issue, a new technique for fault location on transmission lines using only voltage measurements obtained from Wide Area Measurement Systems (WAMS) and the network bus admittance matrix has been reported in this paper. It is based on the fundamental law of electrical networks. It delineates a single step method to find out the faulted line and the exact location of fault. The decision is based on change in injected current at various buses following the line fault. The method has been tested on IEEE 14 bus and New England 39 bus system. Applicability of the proposed algorithm is independent of fault type, location of fault and fault resistance. This method not only proves to be accurate but also furnishes quick results with reduced computational burden. Besides, the faulted phase as well as fault type detection has been suggested in this paper using same measurements. © 2017 Elsevier B.V.